Forget-Me-Nots: Victorian Women, Mourning, and the Construction of a Feminine Historical Memory - Zielke, Melissa (Material Culture Review, 2003)
A study of the Royal Ontario Museum's mourning collection suggests that middle- and upper-middle-class Victorian women used the rituals and accoutrements of this practice to establish and disseminate a meamngful feminine identity and accessible historical memory. Through the transformation of their homes and bodies into sites of memory in honour of friends and family, women were able to realize a myth-making space outside of formal, public commemorative rituals and male-dominated historical discourse. Mourning customs also served as a feminine ritual that allowed forthe validation and transfer of women's traditional skills, knowledge, and sense of self In the process of exploring the shifting meanings of mourning objects in women's lives, particular attention is paid to the experiences of Canadian women. Résumé Une étude de la collection sur le deuil du Musée royal de l'Ontario suggère qu'à l'époque victorienne, les femmes des classes moyennes inférieure et supérieure utilisaient les rituels et attributs de cette pratique pour établt et diffuser une identité féminine significative et une mémoire historique accessible. En transformant leur foyer et leur corps en mémorial de leurs proches, les femmes étaient en mesure de créer un espace mythique en dehors des rituels publics officiels de commémoration et du discours historique à prédominance masculine. Les coutumes de deuil servaient aussi de rituel féminin permettant la validation et le transfert des compétences traditionnelles, des connaissances et du sentiment d'identité des femmes. Le processus d'exploration des significations changeantes des objets de deuil dans l'existence des femmes accorde une attention particulière aux expériences vécues parles Canadiennes.